Digital Assessment in HE: Conceptual Foundations, Applications, and Empirical Evidence - Ismatova, Shakhnoza (The Lingua Spectrum, 2026)
Digital assessment has become a central component of higher education due to technological advancements, expanding online learning environments, and data-driven instructional models. This article examines the conceptual foundations of digital assessment, synthesizes empirical research on its effectiveness, and presents practical applications in university contexts. The literature indicates that digital assessment enhances feedback timeliness, scalability, and adaptive measurement precision. However, concerns regarding validity, academic integrity, equity, and data privacy remain significant. The paper concludes by identifying research gaps and proposing directions for future inquiry in digitally mediated assessment practices.